Introgression of regulatory alleles and a missense coding mutation drive plumage pattern diversity in the rock pigeon - Vickrey, Anna I; Bruders, Rebecca; Kronenberg, Zev; Mackey, Emma; Bohlender, Ryan J; Maclary, Emily T; Maynez, Raquel; Osborne, Edward J; Johnson, Kevin P; Huff, Chad D; Yandell, Mark; Shapiro, Michael D (eLife, 2018)
Birds and other vertebrates display stunning variation in pigmentation patterning, yet the genes controlling this diversity remain largely unknown. Rock pigeons (Columba livia) are fundamentally one of four color pattern phenotypes, in decreasing order of melanism: T-check, checker, bar (ancestral), or barless. Using whole-genome scans, we identified NDP as a candidate gene for this variation. Allele-specific expression differences in NDP indicate cis-regulatory divergence between ancestral and melanistic alleles. Sequence comparisons suggest that derived alleles originated in the speckled pigeon (Columba guinea), providing a striking example of introgression. In contrast, barless rock pigeons have an increased incidence of vision defects and, like human families with hereditary blindness, carry start-codon mutations in NDP. In summary, we find that both coding and regulatory variation in the same gene drives wing pattern diversity, and post-domestication introgression supplied potentially advantageous melanistic alleles to feral populations of this ubiquitous urban bird.
Keywords: Columba livia; pigeon; introgression; NDP; pigmentation; Norrie disease